2012
DOI: 10.1155/2012/328372
|View full text |Cite
|
Sign up to set email alerts
|

The MAPK MEK1/2-ERK1/2 Pathway and Its Implication in Hepatocyte Cell Cycle Control

Abstract: Primary cultures of hepatocytes are powerful models in studying the sequence of events that are necessary for cell progression from a G0-like state to S phase. The models mimic the physiological process of hepatic regeneration after liver injury or partial hepatectomy. Many reports suggest that the mitogen-activated protein kinase (MAPK) ERK1/2 can support hepatocyte proliferation in vitro and in vivo and the MEK/ERK cascade acts as an essential element in hepatocyte responses induced by the EGF. Moreover, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 152 publications
2
32
0
2
Order By: Relevance
“…Indeed, in our study, expression levels of multiple DNA polymerases were downregulated in the eIF5B-KN cells, resulting in the accumulation of nucleotides. Our results also show that eIF5B-KN cells have prolonged S-phase of cell cycle, consistent with previous studies that have shown the involvement of the MAPK pathway in cell cycle regulation [3334]. …”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in our study, expression levels of multiple DNA polymerases were downregulated in the eIF5B-KN cells, resulting in the accumulation of nucleotides. Our results also show that eIF5B-KN cells have prolonged S-phase of cell cycle, consistent with previous studies that have shown the involvement of the MAPK pathway in cell cycle regulation [3334]. …”
Section: Discussionsupporting
confidence: 93%
“…This activation seems to be related to the mammalian sterile-20-like kinase 4, which functions as an enhancer of cell proliferation and invasion through its ability to promote the process of epithelial-mesenchymal transition [32] . ERK2 may play a more prominent role in the proliferation of hepatocytes, while ERK1 may play a pro-apoptotic role [33] . An HCC type having a progenitor cell phenotype may present mechanisms of escaping the pro-apoptotic action of ERK1, which are presumably related to the mutation of p53.…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 and phosphorylated ERK2 are increased in SNTA/B2−/− liver. This MAPK exerts various functions and its activity is enhanced by multiple stimuli [49] which will be identified in ongoing studies. Inhibition of ERK1/2 in primary hepatocytes induces SR-BI protein.…”
Section: Discussionmentioning
confidence: 99%